Cross-Cultural Mission in the Context of Multiple Societies in Indonesia - Peleliu, Herbie. P (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The mission is a divine activity in sending intermediary agents, either supernatural or human, to speak or do God's will to convey the good news to carry out the Great Commission of the Lord Jesus Christ and plural society in Indonesia. The research method used is the descriptive qualitative research method. The research method is used for social and humanities research and theological studies. The results of this study show the importance of evangelism in a pluralistic society with cross-cultural reflection.